معاملي الارتباط المظهري والمرور في هجن نصف تبادلية من التبغ الشرقي (Nicotiana tabacum L.) - معلا محمد; عياش عبد الكريم; المهر نجوى (Latakia University Journal -Biological Sciences Series, 2019)
أجريت هذه الدراسة في ثلاثة مواقع مختلفة الارتفاع عن سطح البحر في محافظة اللاذقية (جب حسن، الحفة، صلنفة) وذلك بهدف تقدير الارتباطات المظهرية بين كل من الصفات الآتية: الوزن الجاف للأوراق، ارتفاع النبات، عدد الأوراق في النبات، المسافة العقدية، الباكورية في الإزهار، نسبة النيكوتين والسكريات في الورقة الوسطى. تم تحليل المسارات لتقدير الأهمية النسبية لتأثير كل صفة في تباين الإنتاجية. تضمنت المادة الوراثية المستخدمة عشرة هجن فردية ناتجة عن التهجين نصف التبادلي بين خمسة أصناف من التبغ الشرقي(Nicotiana tabacum L.). بينت النتائج كلاً من الآتي: ارتباط صفة الوزن الجاف مع كل من ارتفاع النبات وعدد الأوراق ونسبة السكريات في الورقة الوسطى ارتباطاً مظهرياً موجباً في المواقع الثلاث، كما ارتبطت هذه الصفة ارتباطاً مظهرياً موجباً مع صفتي المسافة العقدية، والباكورية في الإزهار في موقعي الحفة وصلنفة. أظهر تحليل معامل المرور للصفات المرتبطة بالوزن الجاف للأوراق في المواقع الثلاثة، أنّ تحسين الغلة يمكن تحقيقه بالاعتماد على ارتفاع النبات (أكثر الصفات مساهمة بالغلة)، وعلى صفة الباكورية في الإزهار، ونسبة السكريات في الورقة الوسطى، والمسافة العقدية، وعدد الأوراق في النبات. استناداً إلى النتائج يمكن اعتبار الصفات المذكورة معايير انتخابية مهمة تساهم بشكل مباشر وغير مباشر في تحسين الغلة لنبات التبغ الشرقي. This study was carried out in three different locations altitude in the province of Latakia (Jeb Hasan, Al Haffe, Slunfeh) in order to estimate the links phenotypic between each of the characters as follows: the dry weight of leaves, plant height, number of leaves, distance between nodes, earliness to flowering, the proportion of nicotine and sugar in the middle leaf. Tracks were analyzed to estimate the relative importance of the effect of each character, in contrast to productivity. The genetic material used included ten individual hybrids resulting from half diallel crosses between five varieties of oriental tobacco (Nicotiana tabacum L.). The results showed the following: dry weight character is linked phenotypic positive with plant height, number of leaves, sugar content in the middle leaf in the three locations. It is also associated phenotypic positive with the characters distance between nodes and earliness to flowering in the locations Al Haffe and Slunfeh. Analysis of the coefficient of the qualities associated with the dry weight of leaves in the three locations, that improving of the yield can be achieved depending on the plant height (the more character contribute to yield), the character earliness to flowering, the percentage of sugar in the middle leaf, the distance between nodes, and number of leaves in the plant. Based on these results, the mentioned characters can be seen as important electoral standards contribute directly and indirectly in improving the yield of the plant oriental tobacco.